2015
DOI: 10.4142/jvs.2015.16.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Normal clinical electroretinography parameters for poodle, Labrador retriever, Thai ridgeback, and Thai Bangkaew

Abstract: The purpose of the present study was to establish normal electroretinogram (ERG) parameters using 56 normal eyes of four dog breeds common in Thailand: poodle, Labrador retriever, Thai ridgeback, and Thai Bangkaew. Standard ERG findings were bilaterally recorded using a handheld multi-species ERG unit with an ERG-jet lens electrode for 28 dogs under preanesthesia with diazepam, anesthesia with propofol, and anesthesia maintenance with isoflurane. There were significant differences in the mean values of ERG amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Another factor to consider is that the corneal electrode used is made for dogs, which have different corneal curvature and globe size when compared with deer. A study comparing ERG in four dog breeds-Poodle, Labrador Retriever, Thai Ridgeback, and Thai Bangkaew -reported that the breed of dog was an important variable in ERG, possibly based on the variation in skull conformation (Sussadee et al, 2015). There was a significant difference of the average body weights for each species in the present study.…”
Section: Discussionmentioning
confidence: 38%
“…Another factor to consider is that the corneal electrode used is made for dogs, which have different corneal curvature and globe size when compared with deer. A study comparing ERG in four dog breeds-Poodle, Labrador Retriever, Thai Ridgeback, and Thai Bangkaew -reported that the breed of dog was an important variable in ERG, possibly based on the variation in skull conformation (Sussadee et al, 2015). There was a significant difference of the average body weights for each species in the present study.…”
Section: Discussionmentioning
confidence: 38%
“…The skull of pharaoh hounds resembles a blunt wedge, and is long and chiseled with only a slight stop and a snout of good length (Coile, 2005). The variations of skull conformation between poodles, Labrador retriever s, Thai Bangkaews, and Thai ridgebacks might be the cause for breed-specific differences in ERG parameters (Sussadee et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…All of that contribute to interfere with the values obtained from ERG recording; therefore, the investigations aiming to establish a normal range still continue. It is recommended each laboratory or clinic to establish a technical procedure that provide reproducible ERG results under specific conditions in order to use the data for diagnostic purposes Sussadee et al, 2015).…”
mentioning
confidence: 99%
“…Esse resultado era esperado e é compatível com estudos de eletrorretinogramas na medicina humana, onde as amplitudes de todas as respostas também apresentam diminuição de valores com a progressão da idade (MCCULLOCH et al, 2015 (GÓES et al, 2015). Outro estudo, que compara quatro raças de cães, também corrobora a variação de amplitude entre diferentes raças (SUSSADEE et al, 2015). Assim, torna-se importante a padronização de respostas entre diferentes raças na análise do exame.…”
Section: Materiais E Métodosunclassified
“…Estudos anteriores indicam a faixa etária como elemento essencial na normatização do exame (SAFATLE et al, 2010a;GÓES et al, 2015), assim como ocorre na eletrorretinografia humana (MCCULLOCH et al, 2015). A raça também mostra-se importante, conforme apurado por Sussadee et al (2015). O uso de fármacos para possibilitar a execução do exame com menor interferência elétrica, decorrente de movimentações musculares, também interfere nos valores obtidos (FREEMAN et al, 2013).…”
Section: Introductionunclassified